1983
DOI: 10.1515/znb-1983-1105
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Pt(II)-Pt(IY) Mixed-Valence Linear Chain Complex: Bis (1,2-diaminopropane )platinum(II)bis (1,2-diaminepropane ) - dibromoplatinum(IV)tetraperchlorate

Abstract: [Pt(C3H10N2)2][Pt(C3H10N2)2Br2](ClO4)4 crystallizes as flat orthorhombic needles with cell dimensions: a = 7.74(1); b = 11.14(2); c = 19.42(3) Å, Z = 1. Since rotation photo­graphs showed diffuse patterns corresponding to odd values of k without any Bragg reflections, the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…In particular, no hint of the occurrence of super-reflections was found down to 11 K. These experimental findings suggest that the diffusions in the k-odd layers are caused by a thermally activated movement of the Br-ions along the chain direction. This anisotropic motion may be described as a 'phonon-like' mode (Cannas, Marongiu, Martin & Keller, 1983;Cannas, Marongiu, Keller, Mfiller & Martin, 1984), as 'mobile valence-alternation domain walls' (Ichinose, 1984), or by similiar dynamic models. In any case: a Br--disordered 'time-averaged' picture of the excited states of the crystal is obtained from the X-ray data at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, no hint of the occurrence of super-reflections was found down to 11 K. These experimental findings suggest that the diffusions in the k-odd layers are caused by a thermally activated movement of the Br-ions along the chain direction. This anisotropic motion may be described as a 'phonon-like' mode (Cannas, Marongiu, Martin & Keller, 1983;Cannas, Marongiu, Keller, Mfiller & Martin, 1984), as 'mobile valence-alternation domain walls' (Ichinose, 1984), or by similiar dynamic models. In any case: a Br--disordered 'time-averaged' picture of the excited states of the crystal is obtained from the X-ray data at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Diffuse patterns, which make the choice of an unambiguous space group more difficult (Beauchamp, Layek & Theophanides, 1982), twinning (Cannas, Marongiu, Keller, Miiller & Martin, 1984) and chiral building blocks (Cannas, Marongiu, Martin & Keller, 1983) are among the difficulties recently discussed in detail. Some of the discrepancies could be resolved by observing the temperature dependence of the 'diffuse patterns' down to 4 K (Cannas, Marongiu, Martin & Keller, 1983;Cannas, Marongiu, Keller, Mfiller & Martin, 1984). On the basis of these data it was proposed that an anisotropic, thermally activated, 'phonon-like' lattice mode-mainly including the chain halides -is responsible for the diffuse patterns.…”
mentioning
confidence: 99%
“…For complexes (3) and (4), which also form an isostructural pair, there is again a space-group problem. Matsumoto et al (1978) determined the structure of the analogous Pt"/Pt ~v chloride and assumed the space group P22~2 v Cannas et al (1983) determined the structure of the analogous bromide and found systematic absences consistent with space groups Pba2 or Pbam, but were unable to distinguish between the two. Our results agree with those of Cannas et al (1983) in that the presence of a and b glides is confirmed.…”
Section: Crystallographymentioning
confidence: 99%
“…Matsumoto et al (1978) determined the structure of the analogous Pt"/Pt ~v chloride and assumed the space group P22~2 v Cannas et al (1983) determined the structure of the analogous bromide and found systematic absences consistent with space groups Pba2 or Pbam, but were unable to distinguish between the two. Our results agree with those of Cannas et al (1983) in that the presence of a and b glides is confirmed. Refinement of the structure of complex (3) in Pba2, which requires the metal atom to occupy a site of symmetry 2 and thus restricts the relative conformations of the two pn ligands to be the same, gave a final R value of 0.026.…”
Section: Crystallographymentioning
confidence: 99%
See 1 more Smart Citation